If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 12 = 12x + 2 Reorder the terms: 12 + 2x = 12x + 2 Reorder the terms: 12 + 2x = 2 + 12x Solving 12 + 2x = 2 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 12 + 2x + -12x = 2 + 12x + -12x Combine like terms: 2x + -12x = -10x 12 + -10x = 2 + 12x + -12x Combine like terms: 12x + -12x = 0 12 + -10x = 2 + 0 12 + -10x = 2 Add '-12' to each side of the equation. 12 + -12 + -10x = 2 + -12 Combine like terms: 12 + -12 = 0 0 + -10x = 2 + -12 -10x = 2 + -12 Combine like terms: 2 + -12 = -10 -10x = -10 Divide each side by '-10'. x = 1 Simplifying x = 1
| 2k+12=2 | | 8=0.5x^4+3x^2 | | (2x+2)(x+1)=1 | | z^2-4iz-29=0 | | p(-2)=x^2-2x | | 2x^-6x/5=6 | | g(-1)=2x^2+5 | | Sin(2*x-pi/2) | | -x=1-x | | 2x(x-3/5)-6 | | 9q-3p+7= | | 3/2*=1/8 | | 5x+9=3x+8 | | 5x+9=3y+8 | | 3y+8=5x+9 | | 7=11 | | y^2dx+(xy+tanxy)dy=0 | | 2x=8/2 | | f(x+2)=3x-4 | | (x-120)*1.8+60=90 | | 1/5x=70 | | 5g-1=3g+4 | | sqrt(17-y)+sqrty(y)=5 | | 3x=5(7) | | 100=x/2*100 | | X=100-(x*15/100) | | 3x+9x-5x= | | -0.12p=2.56+5p | | X=2*10 | | (t)(sqrt(4-t))=0 | | 10n+5=5 | | y=8x^2-6x-14 |